Prediction of Lethality in Suicide Attempts: Gender Matters. (November 2019) - Choo, Carol C.; Harris, Keith M.; Ho, Roger C.
This study explores gender differences in lethality of suicide attempts. Three years of medical records related to suicide attempters ( N  = 666) were subjected to analysis. Of the sample, 69.2% were female, 30.8% male; 63.8% Chinese, 15.8% Indian, and 15.0 % Malay. Ages ranged from 10 to 85 years old ( M  = 29.7, SD  = 16.1). More males than females made attempts with high perceived lethality (χ 2  = 12.10, p  < .0001) and high medical lethality (χ 2  = 10.59, p  < .0001). Available variables were subjected to regression analyses. The regression models predicted more than 60% of high medical lethality suicide attempts and more than 80% of high perceived lethality attempts. Suicide intent and opportunity for rescue were significant predictors for both measures of lethality. Gender differences were examined. Findings were discussed in regard to implications in suicide assessments and interventions.